The Effectiveness of montage play therapy on the development of preschool childrent (5-6 year) in Pembina Jebres Kindergarten - Sensussiana, Titis; Zulaicha S, Endang; Shovie R, Noerma (MEDIA ILMU KESEHATAN, 2024)
Background: Early childhood is when a child is 0–8 years old. The golden age is the age when children experience fast and rapid growth and development. If there is a delay in a step of a child's development, it will affect other developments.. One of the games that can stimulate children's development is montage. Objective: The purpose of this study is to determine the effectiveness of the development of preschool children (5–6 years old) in Pembina Jebres Public Kindergarten.Methods: This research method uses quantitative methods with pre-experimental methods using a one-group pre- and post-test design. Results: The results of this study show that montage play therapy is effective on the development of preschool children (5–6 years old) in Pembina Jebres Public Kindergarten, with proven statistical tests showing a p value <0.000.Conclusion: Parents can do montage therapy to stimulate child development. Educational institutions develop media to stimulate child development with montage techniques